2014
DOI: 10.1371/journal.pone.0104890
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanisms of Sildenafil in Pulmonary Hypertension Involving Cytokines/Chemokines, MAP Kinases and Akt

Abstract: Pulmonary arterial hypertension (PH) is associated with high mortality due to right ventricular failure and hypoxia, therefore to understand the mechanism by which pulmonary vascular remodeling initiates these processes is very important. We used a well-characterized monocrotaline (MCT)-induced rat PH model, and analyzed lung morphology, expression of cytokines, mitogen-activated protein kinase (MAPK) phosphorylation, and phosphatidylinositol 3-kinase-Akt (PI-3k-Akt) pathway and nuclear factor (NF)-κB activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 50 publications
6
34
3
1
Order By: Relevance
“…This is in contrast to a report by Kiss et al ,20 in which sildenafil reduced ERK and p38 activation, and enhanced Akt phosphorylation in a monocrotaline-induced rat PAH model. It is possible that these inconsistencies are due to the different models employed.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to a report by Kiss et al ,20 in which sildenafil reduced ERK and p38 activation, and enhanced Akt phosphorylation in a monocrotaline-induced rat PAH model. It is possible that these inconsistencies are due to the different models employed.…”
Section: Discussioncontrasting
confidence: 99%
“…Arg inhibition decreases the phosphorylation of Akt and ERK1/2. It has been reported that the Akt and ERK pathways are involved in the proliferation pfHPASMCs and progression of PAH (20). Thus, in the present study, the protein expression levels of Akt and ERK in vitro were assessed using western blot analysis.…”
mentioning
confidence: 92%
“…The prognosis of patients with the disease is poor; most untreated patients die within three years due to right-sided heart failure. The main clinical signs and symptoms of PAH include progressive dyspnea with peripheral cyanosis, chest pains, and fatigability [4]. As for our patient, progressive dyspnea and fatigability had been among her principal initial signs and symptoms of PAH before a diagnosis was made.…”
Section: Discussionmentioning
confidence: 57%
“…All clinical features are nonspecific, which is, unfortunately, a frequent cause of delayed detection of the disease [3]. Luckily, however, the incidence of this disease is low-approximately 10 patients per million people [4].…”
Section: Introductionmentioning
confidence: 99%